The use of scenarios for the consolidation of a defense policy - Migon, Eduardo Xavier Ferreira Glaser (2023)
This is a reflection that proposes the relevance of the applicability of prospective scenarios for the improvement of the analysis process for the construction of the Military Force. With a qualitative bias, a deductive perspective was adopted, based on bibliographic research, treated with the support of content analysis. Since war is a concrete social phenomenon, which is expressed on the battlefield, the perspective that Military Sciences approach Applied Social Sciences is corroborated. Therefore, it is suggested that the application of prospective scenarios, resulting from a multidisciplinary analysis, provides elements of reflection that analytically contribute to a more solid study of the Military Force and, therefore, an improvement of the necessary military capabilities to achieve the Objectives. Nationals of a Nation. In this context, the need to devise a coherent methodology for conducting the analyzes and observations collected is highlighted, to avoid the bias and individualism of the conclusions, as well as reporting the gain in the quality of the analyzes with the increase of the scenarios prospects as a substantive factor in the analysis process of the Military Force, essentially, in the definition of the ideal military capabilities.